2007
DOI: 10.1124/jpet.106.118976
|View full text |Cite
|
Sign up to set email alerts
|

The Novel α7 Nicotinic Acetylcholine Receptor AgonistN-[(3R)-1-Azabicyclo[2.2.2]oct-3-yl]-7-[2-(methoxy)phenyl]-1-benzofuran-2-carboxamide Improves Working and Recognition Memory in Rodents

Abstract: The relative contribution of ␣4␤2, ␣7 and other nicotinic acetylcholine receptor (nAChR) subtypes to the memory enhancing versus the addictive effects of nicotine is the subject of ongoing debate. In the present study, we characterized the pharmacological and behavioral properties of the ␣7 nAChR agonist. ABBF bound to ␣7 nAChR in rat brain membranes (K i ϭ 62 nM) and to recombinant human 5-hydroxytryptamine (5-HT) 3 receptors (K i ϭ 60 nM). ABBF was a potent agonist at the recombinant rat and human ␣7 nAChR e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…Moreover, these mutants exhibited performance deficits under baseline conditions in the odor span task, delayed non-match to sample task, win-shift task and attention set-shifting task (Fernandes et al, 2006; Levin et al, 2009; Young et al, 2007; 2011) indicating that perturbations in α7 nAChR signaling influence a wide range of executive processes. Administration of α7 nAChR full/partial agonists or positive allosteric modulators (PAMs) exerted beneficial effects on attention, working and recognition memory, and cognitive flexibility in normal rodents and aged non-human primates (Boess et al, 2007; Bitner et al, 2007; Callahan et al, 2013; Levin et al, 1999; Nikiforuk et al, 2016; Rezvani et al, 2009; Tietje et al, 2008). On the other hand, systemic or intracranial infusions of α7 nAChR antagonist produced impairments in attention and working memory in normal rats (Chan et al, 2007; Hahn et al, 2011; Levin et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these mutants exhibited performance deficits under baseline conditions in the odor span task, delayed non-match to sample task, win-shift task and attention set-shifting task (Fernandes et al, 2006; Levin et al, 2009; Young et al, 2007; 2011) indicating that perturbations in α7 nAChR signaling influence a wide range of executive processes. Administration of α7 nAChR full/partial agonists or positive allosteric modulators (PAMs) exerted beneficial effects on attention, working and recognition memory, and cognitive flexibility in normal rodents and aged non-human primates (Boess et al, 2007; Bitner et al, 2007; Callahan et al, 2013; Levin et al, 1999; Nikiforuk et al, 2016; Rezvani et al, 2009; Tietje et al, 2008). On the other hand, systemic or intracranial infusions of α7 nAChR antagonist produced impairments in attention and working memory in normal rats (Chan et al, 2007; Hahn et al, 2011; Levin et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Systemic α7 agonist treatment has been found to improve cognitive function in a variety of ways. Studies have shown them to attenuate symptoms of schizophrenia (Hauser et al, 2009; Pichat et al, 2007), as well as improve memory (Boess et al, 2007; Prickaerts et al, 2012; Tietje et al, 2008; Van Kampen et al, 2004). The α7 agonist AR-R17779 has been shown to improve learning and memory in rats (Levin et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The α7 subtype of nicotinic acetylcholine receptor (nAChR) has long been considered a potential therapeutic target for treating cogni-tive disorders, and α7-selective drugs have been shown to be effective at improving baseline or compromised behavior in animal models of learning and memory [5,13,27,45,51,53,55]. Drugs targeting α7 have also been identified as effective at reducing inflammation and asso-ciated pain [43,47].…”
Section: Introductionmentioning
confidence: 99%